Identifying Increases in Activity of the Human RVLM Through MSNA-Coupled fMRI - Macefield, Vaughan G.; Henderson, Luke A. (Frontiers in Neuroscience, 2020)
We initially developed concurrent recording of muscle sympathetic nerve activity (MSNA) and functional magnetic resonance imaging (fMRI) of the brain to functionally identify the human homologue of the rostral ventrolateral medulla (RVLM). Here we summarise the cortical and subcortical connections to the RVLM, as identified using MSNA-coupled fMRI. Methods: MSNA was recorded via tungsten microelectrodes inserted into the peroneal nerve. Gradient echo, echo-planar fMRI was performed at 3T (Philips Achieva). 200 volumes (46 axial slices, (TR = 8 s, TE = 4 s, flip angle = 90 o, raw voxel size = 1.5 x 1.5 x 2.75 mm) were collected in a 4s-ON, 4s-OFF sparse sampling protocol and MSNA measured in each 1 s epoch in the 4-s period between scans. Blood Oxygen Level Dependent (BOLD) signal intensity was measured in the corresponding 1 s epoch 4 s later to account for peripheral neural conduction and central neurovascular coupling delays. Results: BOLD signal intensity was positively related to bursts of MSNA in the RVLM, dorsomedial hypothalamus (DMH), ventromedial hypothalamus (VMH), insula, dorsolateral prefrontal cortex (dlPFC), posterior cingulate cortex (PCC), and precuneus, and negatively related in the caudal ventrolateral medulla (CVLM), nucleus tractus solitarius (NTS) and the midbrain periaqueductal gray (PAG). During physiological increases in MSNA (tonic muscle pain), MSNA-coupled BOLD signal intensity was greater in NTS, PAG, DMH, dlPFC, medial prefrontal cortex (mPFC), precuneus and anterior cingulate cortex (ACC) than at rest. During pathophysiological increases in MSNA (obstructive sleep apnoea) signal intensity was also higher in dlPFC, mPFC, ACC and precuneus than in controls. Conversely, signal intensity was lower in RVLM in OSA than in controls, which we interpret as reflecting a withdrawal of active inhibition of the RVLM. Conclusions: These results suggest that multiple cortical and subcortical areas are functionally coupled to the RVLM, which in turn is functionally coupled to the generation of spontaneous bursts of MSNA and their augmentation during physiological and pathophysiological increase in vasoconstrictor drive.